Altered Cerebral Hemodynamics in Early Alzheimer Disease: A Pilot Study Using Transcranial Doppler - Claassen, Jurgen A.H.R. (2009)
Cerebrovascular disease may contribute to the development and progression of Alzheimer’s disease (AD). This study investigated whether impairments in cerebral hemodynamics can be detected in early-stage AD. Nine patients with mild AD and eight cognitively normal controls matched for age underwent brain magnetic resonance imaging and neuropsychological evaluation, followed by assessment of steady-state cerebral blood flow velocity (CBFV, transcranial Doppler), blood pressure (BP, Finapres), and cerebrovascular resistance index (BP/CBFV). Cerebral hemodynamics were quantified using spectral and transfer function analysis of BP and CBFV in rest, during standing up after squat, and during repeated squat-stand maneuvers. Compared to controls, AD patients had lower CBFV and higher cerebrovascular resistance index, unexplained by brain atrophy. Low-frequency variability of BP was enhanced, suggesting impaired arterial baroreflex function. However, CBFV variability was reduced despite enhanced BP variability, and dynamic cerebral autoregulation was not impaired. In conclusion, despite a distinct pattern of altered cerebral hemodynamics, AD patients may have normal autoregulation. However, the challenges for autoregulation in AD are higher, as our data show enhanced BP fluctuations. Increased cerebral vasoconstriction or reduced vasomotion also may attenuate CBFV variability.